Study guide: HBEC3203 Child Psychology - Badzis, Mastura (Open University Malaysia (OUM), 2012)
This course enables students to understand child psychology and development from the prenatal period through adolescence. Major theories and the development aspects of the child’s intellectual, emotional social and physical growth are presented. The impact of psychological and biological factors on the child is also examined to be applied in the process of care, development and learning in the context of early childhood.